Coupling influences of elevated temperature and strain rate on the behaviour of 6061-T6 aluminium alloy used as construction material. (June 2022) - Zhang, Hao-Ran; Zhao, Hui; Wang, Rui; Liang, Xiang-Xiang; Zhu, Yong
Abstract: This work investigates the dynamic compressive behaviours of 6061-T6 aluminium alloy under varying temperatures (25, 100, 200, 250 and 300 °C) and strain rates of 0.001–4732 s −1, which is essential to analyse the performance of aluminium structures subjected to combined actions of fire and explosion/impact. Therefore, the static compression and dynamic impact experiments using a Split-Hopkinson Pressure Bar (SHPB) were performed at elevated temperatures and the microstructural evolution of the tested specimens was examined. Based on these tests, the stress–strain relationships, influences of temperatures and strain rates as well as microstructures were discussed. Experimental results indicated that the dynamic mechanical performance of 6061-T6 alloy significantly depends on the temperature. In addition, a significant strain rate effect is found when the strain rate varies between 581 s −1 and 2109 s −1 . The observation of microstructures presented that the grain size rises with an increasing temperature or a declining strain rate. Finally, the modified Johnson-Cook (J-C) model was suggested to describe the stress–strain responses and could give an acceptable prediction.